Ambiente institucional e intercooperação em cooperativas de crédito brasileiras: um estudo de caso na Cooperativa Sicredi União Metropolitana RS - Oliveira, Vinícius de (Universidade do Vale do Rio dos Sinos, 2021)
This study deals with the intercooperation in credit unions and the Brazilian institutional environment. This work aims to analyze how intercooperation can help credit unions to deal with the Brazilian institutional environment, in the case of Cooperativa Sicredi União Metropolitana RS. In methodological terms, a single case study was carried out through exploratory and descriptive qualitative research through the application of semi-structured interviews. Among the interviewed subjects are 2 managers, 3 directors, the vice president and a president of the Sicredi União Metropolitana RS cooperative. For data treatment, content analysis was adopted with the aid of the Nvivo software. From the literature review, the interview script was constructed and the 13 a priori categories were defined, from which the final categories emerged. Among the main empirical findings identified in this research are the positive characteristics of intercooperation. It is pointed out that organizational learning allowed the exchange of information and experiences between credit unions. It is also noteworthy that the fact that the cooperatives belong to a system caused a gain in potential, scale and business growth. It was identified that another advantage of the cooperatives belonging to a system is the centralization of meeting legal demands, since this whole process is centralized with the system. The research pointed out that the exchange of experiences between the cooperatives promotes the use of best practices in the processes, where the mistakes and successes generate lessons learned that allow a more effective performance, through the practice of intercooperation. The results highlight the advantages of intercooperation, including greater security in meeting the legal demands of the Brazilian institutional environment, through standardized procedures and a team of specialists. The research showed that intercooperation helps the cooperative belonging to a system to be competitive, providing a strong brand and media and gaining scale in products and services. On the other hand, the research identified some difficulties that cooperatives may have because they are not incorporated into a system and, consequently, do not exercise the practice of intercooperation. Among the disadvantages are a greater difficulty in starting activities, little capacity for large investments, as well as a complexity for the entry of large centers into the market. Thus, the contributions highlighted in this research covered the analysis of how intercooperation can help credit unions to deal with the Brazilian institutional environment. Thus, the motivators for intercooperation were identified, describing the characteristics of the Brazilian institutional environment, as well as the identification of institutional variables that drive or are restrictive to intercooperation, proposing a model for intercooperation in credit unions.
Keywords: Cooperativismos; Cooperativa de crédito; Intercooperação; Teoria institucional; Ambiente institucional; Cooperatives; Credit cooperative; Intercooperation; Institutional theory; Institutional environment; ACCNPQ::Ciências Sociais Aplicadas::Administração